2022
DOI: 10.1073/pnas.2205629119
|View full text |Cite
|
Sign up to set email alerts
|

LAPTM5 mediates immature B cell apoptosis and B cell tolerance by regulating the WWP2-PTEN-AKT pathway

Abstract: Elimination of autoreactive developing B cells is an important mechanism to prevent autoantibody production. However, how B cell receptor (BCR) signaling triggers apoptosis of immature B cells remains poorly understood. We show that BCR stimulation up-regulates the expression of the lysosomal-associated transmembrane protein 5 (LAPTM5), which in turn triggers apoptosis of immature B cells through two pathways. LAPTM5 causes BCR internalization, resulting in decreased phosphorylation of SYK and ERK. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, it is known that cellular EPS biosynthesis is not only related to the transcription and translation processes but also the supply of EPS building blocks (e.g., amino acids), which are regulated by many functional proteins, such as the transcriptional regulator and amino acid synthase according to KEGG, GO, and COG databases. Thereby, the response of the functional protein level to ammonia stress was investigated by label-free proteomics, which was one of the most advanced mass spectrometry techniques to identify cellular functional proteins. ,, The proteomic data in Figure E clearly shows that ammonia stress significantly reduced the expressions of vital proteins in charge of EPS synthesis to 0–0.83-fold compared to that of the control. Notably, the transcriptional module, such as the DNA-directed RNA polymerase subunit Rpo 10, and the translation module, such as pyrrolysine-tRNA ligase, were the pivotal regulators of the transcription and translation processes, which transcribed DNA into mRNA, and then synthesized proteins using aminoacyl-tRNA substrates with mRNA as the template. , Also, the enzymes for amino acid synthesis, including tryptophan synthase, could provide the building blocks for EPS synthesis and assembly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is known that cellular EPS biosynthesis is not only related to the transcription and translation processes but also the supply of EPS building blocks (e.g., amino acids), which are regulated by many functional proteins, such as the transcriptional regulator and amino acid synthase according to KEGG, GO, and COG databases. Thereby, the response of the functional protein level to ammonia stress was investigated by label-free proteomics, which was one of the most advanced mass spectrometry techniques to identify cellular functional proteins. ,, The proteomic data in Figure E clearly shows that ammonia stress significantly reduced the expressions of vital proteins in charge of EPS synthesis to 0–0.83-fold compared to that of the control. Notably, the transcriptional module, such as the DNA-directed RNA polymerase subunit Rpo 10, and the translation module, such as pyrrolysine-tRNA ligase, were the pivotal regulators of the transcription and translation processes, which transcribed DNA into mRNA, and then synthesized proteins using aminoacyl-tRNA substrates with mRNA as the template. , Also, the enzymes for amino acid synthesis, including tryptophan synthase, could provide the building blocks for EPS synthesis and assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, the response of the functional protein level to ammonia stress was investigated by label-free proteomics, which was one of the most advanced mass spectrometry techniques to identify cellular functional proteins. 9,53,54 The proteomic data in Figure 6E clearly shows that ammonia stress significantly reduced the expressions of vital proteins in charge of EPS synthesis to 0−0.83-fold compared to that of the control. Notably, the transcriptional module, such as the DNA-directed RNA polymerase subunit Rpo 10, and the translation module, such as pyrrolysine-tRNA ligase, were the pivotal regulators of the transcription and translation processes, which transcribed DNA into mRNA, and then synthesized proteins using aminoacyl-tRNA substrates with mRNA as the template.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Is it possibly because that treatment with 50 µM CQ failed to inhibit lysosomal degradation in HUVECs. To determine whether treatment with 50 µM CQ inhibited lysosomal degradation in HUVECs, HUVECs were transfected with expression plasmids encoding HA-WWP2, with or without Ub K63, and then treated with 0, 20, 50, 100 μM CQ for 24 h. Previous research has reported that WWP2 can be degraded through the lysosome pathway [ 55 ]. As shown in Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LAPTM5, a multifunctional protein, has been implicated in several cellular processes, including autophagy [ 50 ], lysosomal stabilization [ 51 ], apoptosis [ 52 ], and inflammation [ 23 , 53 ]. Its role as a pro-inflammatory factor has been well-established in macrophages [ 53 ] and myocardial infarction [ 23 ].…”
Section: Discussionmentioning
confidence: 99%